Hyperbolic discounting and the Phillips curve - Liam Graham; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2007)
Using a standard dynamic general equilibrium model, we show that the interaction of staggered nominal contracts with hyperbolic discounting leads to inflation having significant long-run eects on real variables.
Keywords: E20; E40; E50; 330; Unemployment; Phillips curve; Monetary policy; Dynamic general equilibrium; Nominal inertia; Inflation; Phillips-Kurve; Lohnrigidität; Dynamisches Gleichgewicht; Geldpolitik; Theorie